The cult of the earth, the mountains and the water. Similarities between the Andes and Mesoamerica - Limón Olvera, Silvia (2005)
Both the Andean and Mesoamerican peoples were characterized by having agriculture as the main economic activity, which, according to ancient religious ideas, was controlled by various sacred beings personified as deities. The dependence of these societies on certain supernatural entities that decided the production of sustenance gave rise to the sacralization of some elements of nature and to consider the need to dedicate constant ceremonies to them to promote the proper development of crops.